ANALYSIS AND IDENTIFICATION OF DNA SEQUENCE VARIATIONS IN Cyprinus carpio IN LAKE KERINCI - Tomi Apra Santosa; Abdul Razak; Eria Marina Septiyani (BIOEDUKASI, 2021)
This study aims to find out the analysis and identification of variations in DNA sequences in Cyprinus carpio in Lake Kerinci. 7. Research using qualitative research type with a literature study method. Data sources come from national and international journals. The results of the study can be concluded that Cyprinus carpio Cyprinus carpio has a varied gene that the number of DNA chromosomes 48 pairs or 2n = 96 who have DNA sequence analysis 5' GCCTTCGTGGCCCTTCCCAC-3' and 5'- GGTTGCTCCTGTCCGCCACCCC-3' and has three microsatellite eloquence, MHF6, MFW7, and MFW9